Perlindungan Hak Pekerja Perempuan di Perkebunan Kelapa Sawit Perseroan Terbatas Citra Putra Kebun Asri (PT. CPKA) Kecamatan Jorong Kabupaten Tanah Laut - Rahmah Rahmah (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2015)
This study examines the Protection of Women's Rights Workers in Oil Palm Plantation PT. CPKA Jorong District Tanah Laut regency. Protection of women workers who examined include Company policy PT. CPKA Jorong District Tanah Laut regency to protection of health and safety (K3) protection of women workers and women workers' wages.The research method selected is a qualitative method of data capture techniques through observation, interview and documentation. Sources of data drawn from interviews with informants and appropriate documentation of research objects and analyzed by data reduction, data display and conclusion. Tested the validity of data obtained by the extension of the observations, increasing persistence, triangulation and member checks conducted.The results showed that the protection of health and safety protection of women workers in the company PT.CPKA not be implemented to the fullest. Wage system given PT.CPKA company is referring to the plantation Sectoral Minimum Wage (UMS-P). Given the amount of wages PT. CPKA is above of the Minimum Wage (UMR).Based on the results of this study suggested that women workers should have the education, insight, and knowledge is quite extensive, particularly on the provisions of the laws that protect their rights as women workers and the company should provide facilities for the employment protection workers especially women workers and the company is expected to be even more effective in the dissemination of regulations that protect the rights of women workers.Keywords: Protection, Rights, Women Workers